Stability Studies of Crude Plant Material of Bacopa monnieri and Its Effect on Free Radical Scavenging Activity - Hemalata M. Puntambekar1, Anuradha S. Upadhye2 and Anagha C. Desai3, Pratibha Srivastava1*, Hema N. Raut1, (Journal of Phytology, 2010)
Stability study of the crude plant material of Bacopa monnieri has been carried out as per ICH guidelines and its effect on free radical scavenging activity was studied by DPPH, ABTS radical scavenging assays and Deoxyribose degradation assay. The dried whole plant material of B. monnieri was kept in stability chambers at 40Â°C and 75% relative humidity in case of accelerated studies and at 30Â°C and 65% relative humidity for long term studies. Real time studies samples were stored at room temperature. Samples were taken out at periodic intervals, extracted in methanol to observe the HPTLC profiles and to study free radical scavenging activity. Results of antioxidant assays indicated that the samples of long term studies showed better antioxidant activity than the samples of accelerated and real time studies. Key words: Brahmi; accelerated study; long term study; real time study; free radical scavenging activity Abbreviations: BM: Bacopa monnieri; AS: Accelerated studies; LS: Long term studies; RT Real time studies <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Pratibha Srivastava et al. Stability Studies of Crude Plant Material of Bacopa monnieri and Its Effect on Free Radical Scavenging Activity. J Phytol 2/8 (2010) 103-109.